Challenges and strategies of a freelance translator in translating journalistic content: A qualitative case study - Afifah Zahrah Juliandini; Yohannes Telaumbanua; Kotrini Kotrini (UNIB Press, 2026)
This research presents an analysis of challenges and strategies in translating journalistic content, which demands accuracy, speed, and sensitivity to cultural context. Because of these characteristics, translating journalistic texts require different skills and approaches compared to other types of texts. Unlike translator-journalists who find journalistic texts as part of their daily work, freelance translators, who are generally more familiar with literary, legal, advertising and marketing, medical, and business texts often faces unique difficulties due to the concise and clear nature of journalistic writing. These challenges require careful attention to semantic, syntactic, and pragmatic elements to ensure that meaning is effectively conveyed to the target audience. The main objective of this study is to identify and analyze the specific challenges faced by freelance translator when translating journalistic content for the first time and to explore the strategies used to address them. The study also aims to provide insights that can contribute to a broader understanding of translation practices in a journalistic context. A single case study design is used by involving a single freelance translator with two years of experience in translating academic writings, literary works, and promotional texts. Data were collected through in-depth interviews and analyzed using thematic analysis by Braun and Clarke (2006). The analysis revealed four key challenges: accuracy and readability, cultural nuance, bias and framing, and deadline pressures. To overcome these challenges, four main strategies are used: adaptation, localization, transcreation, and selective omission and addition. The findings reveal that freelance translators need a combination of linguistic skills, cultural sensitivity, and effective time management to produce credible, reliable, and accurate translations.